2017
DOI: 10.15761/hce.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological effect of Lamivudine on the Cerebellum of Wistar rats

Abstract: Lamivudine is an anti-retroviral drug used for the treatment of HIV and hepatitis B. It is one of the essential medicines needed in a basic health system. This study was carried out to investigate the detrimental effect of lamivudine on the cerebellum based on the adverse effects of gait disorders manifested by patients using lamivudine. Twenty male Wistar rats divided into two groups of ten rats each were used for the study. Control group A was administered with 1ml of distilled water, while treatment group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Tenofovir and lamivudine treated groups produced significant distortion of the cortical histomorphology. These results are in tandem with Ferrer and Rakhmanina (2013) who reported peripheral neuropathy in mice treated with tenofovir and the study of Peter et al (2017) who reported shrunken Purkinje cells and distorted granular layer in the cerebellum of rats treated with lamivudine. Several studies highlighting the detrimental effects that antiretroviral drugs have on neural structures are often through mechanisms involving oxidative stress.…”
Section: Discussionsupporting
confidence: 83%
“…Tenofovir and lamivudine treated groups produced significant distortion of the cortical histomorphology. These results are in tandem with Ferrer and Rakhmanina (2013) who reported peripheral neuropathy in mice treated with tenofovir and the study of Peter et al (2017) who reported shrunken Purkinje cells and distorted granular layer in the cerebellum of rats treated with lamivudine. Several studies highlighting the detrimental effects that antiretroviral drugs have on neural structures are often through mechanisms involving oxidative stress.…”
Section: Discussionsupporting
confidence: 83%
“…Highly active antiretroviral therapy is used for management of HIV/AIDS, and the devastating effect of HIV required infected individual to use HAART for the management of the virus, especially in Africa where HIV is predominant ( World Health Organization, 2021 , Joint United National Programme on HIV/AIDS (UNAIDS), 2021 ). Many studies ( Peter and Udoh, 2015 , Peter et al, 2017 , Lawal et al, 2021 ) have mentioned that antiretrovirals drugs are neurotoxic and can lead to various neurologic diseases including memory impairment and cognitive disorder ( Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellum could be considered particularly vulnerable to different antivirals. A previous study suggested that the administration of lamivudine, an antiviral drug used in treatment of HIV and hepatitis B viruses, lead to an evident cerebellar degeneration (Peter, Udoh, & Ekanem, 2017).…”
Section: Introductionmentioning
confidence: 99%